Foliar application of boron and ethephon on postharvest ripening and conservation of 'Galaxy' apples - Anese, Rogerio de Oliveira; Andrade , Eliton Dines Ribeiro de (Revista de Ciências Agroveterinárias, 2025)
Boron (B) and ethephon have been used in preharvest foliar sprays to anticipate the ripening of apples (Malus domestica Borkh.), however there are reports of potential negative effects during the post-harvest conservation of the fruits. In this context, the objective of this study was to evaluate the effects of preharvest foliar application of boron and ethephon on the maturation and conservation capacity of 'Galaxy' apples in refrigerated storage for four months plus seven days of shelf life at 15ºC. The experiment was conducted in a commercial orchard in the municipality of Urupema - SC, Brazil during the 2020/2021 harvest. The experimental design used was of randomized blocks, with four treatments and three replications. The treatments were applied via foliar during preharvest as follows: control (no application); boron 3g L-1 (4 applications); boron 3g L-1 + ethephon 300mg L-1 and ethephon 300mg L-1. The attributes related to quality and conservation of the fruits at harvest were determined in two stages with an interval of ten days, and after storage. Fruit maturation was anticipated by preharvest foliar application of boron and ethephon, without changing the background color and red intensity of the epidermis. There was a reduction in pulp firmness as a function of the treatments after refrigerated storage for four months. Thus, both products can be an alternative for staggering of harvest, but the commercialization of fruits treated and stored in refrigerated storage must be done in advance due to the reduction in pulp firmness.